Confidence - Denny, Richard; Lake, Nick; Turner, Barry; Gawith, Paul ([S.l.] : Man Management Ltd. [production company] ; Kuala Lumpur : First Training [distributor])
The story is about building a confidence in every manager to handle and manage the company
Copy available in DVD format
Camera, Mark Lipscomb ; sound supervisor, Bill Cadman ; lighting director, Nigel Fisher
Keywords: Confidence; Executives; Self-confidence